Selection and Adaptation to Urban Food Resources Promote Spotted Dove (Streptopelia chinensis) as a Common Species in Urban Habitats - Mengjie Lu; Xueli Zhang; Jiahan Ruan; Wanyou Li; Mingwang Chen; Long Ma; Zhen Zhang; Bicai Guan; Luzhang Ruan (Ecology and Evolution, 2025)
ABSTRACT Rapid urban development has almost completely reshaped the original landscape. Then birds are required to adapt to urban food resources for their survival in the city. In recent years, spotted doves have become increasingly common in urban habitats, but their dietary composition and variation are unclear. The DNA metabarcoding technique was applied to identify the primary food components of spotted doves (Streptopelia chinensis) in Nanchang, China. A total of 100 plant species were identified from 251 spotted dove fecal samples throughout four seasons (2020–2021). Spotted doves foraged Cinnamomum camphora seeds assigned to the Lauraceae family in the highest proportion throughout the year, suggesting that urban spotted doves mainly depend on artificial greening plants as their main food source. Furthermore, the dietary composition of spotted doves varied with increasing or decreasing plant resources. In spring, spotted doves primarily consumed Gramineae plants when they were growing and seed‐bearing, while foraging the seeds of Kummerowia striata first in autumn. Although Cinnamomum camphora seeds were available in a year, which provided the conserved food, spotted doves would first choose to forage on fresh and high‐quality plants when food resources were adequate and stable. Our study confirmed that spotted doves can make use of urban food resources, but we still recommend maintaining the diversity of plants when greening to provide more food choices for urban birds. That will promote the survival of birds in urban habitats, resulting in a city where humans and birds coexist harmoniously.